Pengaruh Employer Attractiveness dan Use of Social Media terhadap Intention to Apply Generasi Z pada PT XYZ Bandung - Aisna Dewi Romizza; Ratih Purbasari; Dian Fordian (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
Competition to attract young talent in the digital era encourages companies to strengthen their Employer Attractiveness while also using social media as a recruitment communication channel. This study examines the effect of Employer Attractiveness and Use of Social Media on Generation Z's Intention to Apply at Company X, a food and beverage (F&B) company in Bandung. The study was motivated by a three-year decline in the number of job applications received by the company. A quantitative approach with a verificative survey design was employed. Data were collected from 97 Generation Z respondents who were familiar with the company through social media, selected using purposive sampling, and analysed with multiple linear regression supported by the F-test, t-test, and coefficient of determination. The results show that Employer Attractiveness and Use of Social Media each have a positive and significant effect on Intention to Apply, both partially and simultaneously, with Employer Attractiveness exerting a stronger influence than Use of Social Media. Together, the two variables explain 69.6% of the variance in Intention to Apply. These findings suggest that strengthening a company's image as an employer, supported by effective social media management, can increase Generation Z's Intention to Apply for jobs at Company X.